KONSEP KECERDASAN EMOSIONAL (Tinjauan Pendidikan Islam) - Maryam, maryam (AZKIYA, 2018)
This research aims to identify an overview of the concept of emotional intelligence in the review of Islamic education. The concept of the emotional intelligence is taken from several literatures that concern and related to almost all of the content of the emotional intelligence. This research is library research with a philosophical approach that is studied both from language analysis and concept analysis. Daniel Goleman has divided it into five basic emotional skills; self-awareness, managing emotions, utilizing emotions productively, empathy: reading emotions, building relationships. The result of the study shows that almost all the content of emotional intelligence concept has meeting point that deal with Islamic education. As a result, this matter is used as a guideline in achieving the success of Islamic education. So that the output of the Islamic education that is produced can be formed people as whole human being.